Invariance to background noise as a signature of non-primary auditory cortex - Alexander J. E. Kell (Nature Portfolio, 2019)
The authors show that areas of the auditory cortex differ in the extent to which their responses to sounds are altered by the presence of background noise. Cortical responses to sounds in primary areas are more affected by background noise than are those in non-primary areas.